Als die Filme laufen lernten - Gabriel Hege and Thomas C. Schmidt and Matthias Wählisch and Hans L. Cycon and Mark Palkow (TERENA, 2009)
In recent years, video conferencing solutions have started to become available as an end-to-end service on personal devices, and are now on the spot to enter the class of mobile smartphones. In this paper we report on advanced mobility services of our video conferencing software. Based on emerging standards in SIP signaling and scalable H.264 video compression, the solution supports for a seamless integration of mobile smartphones into group conferences, and in particular extends group conference management to comply with session mobility. While remaining on a conference call, a user is thus enabled to shift his presence from a stationary end system to a mobile, and continue the conversation while leaving the office.